The real Jane Austen : a life in small things - Byrne, Paula. author (New York : Harper)
"This new biography explores the forces that shaped the interior life of one of the most beloved novelists in the English language....each chapter begins by evoking an object that conjures up a key moment or theme in Austen's life and work.... The woman who emerges is far tougher, more socially and politically aware, and altogether more modern that the conventional picture.... The book looks closely, too, at the biographical influences on her work, as well as her boundless wit and energy...."--Dust jacket.